Esophageal Doppler Can Predict Fluid Responsiveness Through End-Expiratory and End-Inspiratory Occlusion Tests. Issue 2 (February 2019) - Dépret, François; Jozwiak, Mathieu; Teboul, Jean-Louis; Alphonsine, Jean-Emmanuel; Richard, Christian; Monnet, Xavier
Abstract : Objectives: To assess whether, in patients under mechanical ventilation, fluid responsiveness is predicted by the effects of short respiratory holds on cardiac index estimated by esophageal Doppler. Design: Prospective, monocentric study. Setting: Medical ICU. Patients: Twenty-eight adult patients with acute circulatory failure and a decision of the clinicians in charge to administer fluids. Interventions: Before and after infusing 500 mL of saline, we measured cardiac index estimated by esophageal Doppler before and during the last 5 seconds of successive 15-second end-inspiratory occlusion and end-expiratory occlusion, separated by 1 minute. Patients in whom volume expansion increased cardiac index measured by transpulmonary thermodilution greater than or equal to 15% were defined as "fluid responders." Cardiac index measured by the Pulse Contour Cardiac Output device (from pulse contour analysis or transpulmonary thermodilution) was used as the reference. Measurements and Main Results: End-expiratory occlusion increased cardiac index estimated by esophageal Doppler more in responders than in nonresponders (8% ± 2% vs 3% ± 1%, respectively; p < 0.0001) and end-inspiratory occlusion decreased cardiac index estimated by esophageal Doppler more in responders than in nonresponders (–8% ± 5% vs –4% ± 2%, respectively; p = 0.0002). Fluid responsiveness was predicted by the end-expiratory occlusion induced percent change in cardiac index estimated by esophageal Doppler with an area under the receiver operating characteristic curve of 1.00 (95% CI, 0.88–1.00) and a threshold value of 4% increase in cardiac index estimated by esophageal Doppler. It was predicted by the sum of absolute values of percent changes in cardiac index estimated by esophageal Doppler during both occlusions with a similar area under the receiver operating characteristic curve (0.99 [0.86–1.00]) and with a threshold of 9% change in cardiac index estimated by esophageal Doppler, which is compatible with the esophageal Doppler precision. Conclusions: If the absolute sum of the percent change in cardiac index estimated by esophageal Doppler induced by two successive end-inspiratory occlusion and end-expiratory occlusion maneuvers is greater than 9%, it is likely that a 500 mL fluid infusion will increase cardiac output. This diagnostic threshold is higher than if only end-expiratory occlusion induced percent changes in cardiac index estimated by esophageal Doppler are taken into account. Abstract : Supplemental Digital Content is available in the text.